Der ägyptische Lautwandel zwischen ‘ und m - Bojowald, Stefan.
In this article, the Egyptian phonetic change between a and m is considered once again. Research so far has discussed the writing […] for the ’m’’-drug as the only evidence for the phenomenon. Here, the number of examples is successively increased, to which end the work is separated into two parts. In the first one, five new writings are introduced, which have been influenced by the phonetic change. In the second part, a number of plays on words is presented, including this phonetic change.